A demographic analysis of delighters of b2c website storefronts (what surfers mistakenly think are not important features of B2C storefronts). - Atienza, Rumel V. (Philippine Industrial Engineering Journal)
B2C websites that are able to show in comparative format their product's pictures, prices and features, or have color combination of blue and white are more likely to be patronized. This is found to be true regardless of sex and age.